Three dimensional reconstructions of Nummulites tests reveal complex chamber shapes - Renema, Willem (PeerJ, 2015)
Larger benthic foraminifera (LBF) are important and prolific carbonate producers both in modern and ancient shallow tropical seas. During the Paleogene the genus Nummulites was particularly abundant with a global distribution, leading it to be frequently used in biostratigraphy. However, their evolution is poorly understood as classification is Europe-centered and mostly based on external characters and equatorial thin sections. New occurrences from regions outside the northern Tethys which poorly fit in thus reference frame, show that a more rigid framework for the classification of Nummulites is needed. Here we apply micro computed-tomographical scanning, a tool that recently has become available, to visualise 3D chamber shape of Nummulites djokdjokartae and compare these to traditional morphometrical characters. We find that despite the regular shape in equatorial and axial thin section the irregular 3D chamber shape is not predicted by these sections. We argue that 3D reconstructions of Nummulites tests will be a great aid in improving our understanding of lineages within the genus Nummulites, and to elucidate its evolutionary and biogeographical history.